2022
DOI: 10.1093/heapro/daac134
|View full text |Cite
|
Sign up to set email alerts
|

Predicted and observed impacts of COVID-19 lockdowns: two Health Impact Assessments in Scotland and Wales

Abstract: Health Impact Assessment is a key approach used internationally to identify positive or negative impacts of policies, plans and proposals on health and well-being. In 2020, HIAs were undertaken in Scotland and Wales to identify the potential health and well-being impacts of the ‘stay at home’ and physical distancing measures implemented at the start of the coronavirus disease (COVID-19) pandemic. There is sparse evidence evaluating whether the impacts predicted in HIAs occur following policy implementation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The societal effects of the COVID-19 pandemic, including social distancing measures, have had a lasting impact on well-being, including social interaction and isolation, as well as reducing access to services (Dahlgren & Whitehead, 2021;Green et al, 2022). Within Wales, certain population groups have been particularly impacted, including socially deprived communities, older people and those on low incomes (Green et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The societal effects of the COVID-19 pandemic, including social distancing measures, have had a lasting impact on well-being, including social interaction and isolation, as well as reducing access to services (Dahlgren & Whitehead, 2021;Green et al, 2022). Within Wales, certain population groups have been particularly impacted, including socially deprived communities, older people and those on low incomes (Green et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The societal effects of the COVID-19 pandemic, including social distancing measures, have had a lasting impact on well-being, including social interaction and isolation, as well as reducing access to services (Dahlgren & Whitehead, 2021;Green et al, 2022). Within Wales, certain population groups have been particularly impacted, including socially deprived communities, older people and those on low incomes (Green et al, 2022). In response, public services, including the police and local government workers, are increasingly employing a public health trauma-informed and preventative approach to helping communities (Jones, 2020;Snowdon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We showed that although acceptance and adoption can be measured, adherence is influenced by multiple cofounding factors. Here, adherence to the All Wales COVID-19 hospital guidelines was likely also influenced by local pathways (even geographical layout of hospitals), other national guidance including NICE (424) and WHO (425), lock down (426,427), background comorbidities and health inequality in Wales (428), clinical capacity, and capabilities (as some systems became overwhelmed) (429), as well as policy learnings from experiences of other countries (430,431).…”
Section: Strengthsmentioning
confidence: 99%